A Study on the Cross-Cultural Management of China's Haier Group in its UK Branch - YU, NIHAN (2018)
With the globalisation of world business, cross-cultural management issues have emerged, as a result of which multinational companies are facing great challenges in terms of cultural differences. This paper takes China’s Haier Group as an example and mainly studies the cross-cultural management of Haier in its UK branch. The major objective of this research is to explore the factors influencing the cross-cultural management of Haier UK, along with the problems it faces in the process of handling Chinese-English cultural differences.